VD_FINDINFO Décision / 2012 / 692 vom 24. Mai 2012 - VD Tribunal cantonal (2012)
DÉFENSE D'OFFICE, ASSISTANCE JUDICIAIRE, DÉFENSE NÉCESSAIRE | 130 let. b CPP (CH), 132 CPP (CH), 393 al. 1 let. a CPP (CH)